Relevance of Chronic Lyme Disease to Family Medicine as a Complex Multidimensional Chronic Disease Construct: A Systematic Review. (23rd November 2014) - Borgermans, Liesbeth; Goderis, Geert; Vandevoorde, Jan; Devroey, Dirk
Abstract : Lyme disease has become a global public health problem and a prototype of an emerging infection. Both treatment-refractory infection and symptoms that are related to Borrelia burgdorferi infection remain subject to controversy. Because of the absence of solid evidence on prevalence, causes, diagnostic criteria, tools and treatment options, the role of autoimmunity to residual or persisting antigens, and the role of a toxin or other bacterial-associated products that are responsible for the symptoms and signs, chronic Lyme disease (CLD) remains a relatively poorly understood chronic disease construct. The role and performance of family medicine in the detection, integrative treatment, and follow-up of CLD are not well studied either. The purpose of this paper is to describe insights into the complexity of CLD as a multidimensional chronic disease construct and its relevance to family medicine by means of a systematic literature review.